2005
DOI: 10.4315/0362-028x-68.2.396
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Pathogens Inoculated into Prepared Seafood Products for Manufacturing Kimbab, Steamed Rice Rolled in Dried Seaweed, by Gamma Irradiation

Abstract: Three prepared seafood products for manufacturing a laver (dried seaweed) roll, a traditional and rapidly growing ready-to-eat meal in Korea, were selected and the effects of irradiation treatment for eliminating pathogens of public health significance were investigated. The pathogens tested were Salmonella Typhimurium, Escherichia coli, Staphylococcus aureus, and Listeria ivanovii. The radiation sensitivity (D10-values or the dose required to inactivate 90% of a population) of these organisms ranged from 0.23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…These results were consistent with the study of (16) who found that the four bacterial isolates recovered from six different honey samples produced by three native bee species in Northern Thailand were either, gram-negative or gramvariable, short rod bacteria, which is a typical character of acetic acid bacteria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results were consistent with the study of (16) who found that the four bacterial isolates recovered from six different honey samples produced by three native bee species in Northern Thailand were either, gram-negative or gramvariable, short rod bacteria, which is a typical character of acetic acid bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…Bee honey is usually contaminated with numerous microorganisms, among these osmophilic yeast predominates, mainly the strains of Saccharomyces, Schizosaccharomyces and Torula. In bee honey, aerobic Bacillus and anaerobic Clostridium spores as well as spores and small fragments of moulds may appear (16) .…”
Section: Introductionmentioning
confidence: 99%
“…Coagulase positive staphylococci was isolated in 15 of 20 (75%) meatball samples, 20 of 20 (100%) cooked liver samples, and 20 of 20 (100%) Russian salad samples, at the level of 3.5, 4.9 and 5.1 log CFU/g, respectively (Ö ner, 1997). Jo et al (2005) reported that S. aureus inoculated into prepared seafood products including imitation crab leg, surimi gel and dried laver was not detected after 3 kGy of a gamma irradiation. Table 5 shows the calculated D 10 value of the irradiation treatment of the Kimbab tested.…”
Section: Resultsmentioning
confidence: 96%
“…Lee et al (2005) reported that most contamination of Kimbab was caused by food materials such as dried laver, surimi gel, seasoned and blanched spinach, and cucumber. Jo, Lee, Kang, et al (2004) and Jo et al (2005) have studied the food materials for Kimbab manufacturing and reported that low dose irradiation (less than 3 kGy) can eliminate pathogens inoculated into readyto-use foods originated from animal and seafood. The objective of the present study was to demonstrate the efficacy of irradiation treatment for eliminating the pathogens such as Salmonella Typhimurium, Escherichia coli, S. aureus and Listeria ivanovii in a manufactured Kimbab, thereby ensuring the microbiological safety of the ready-to-eat Kimbab.…”
Section: Introductionmentioning
confidence: 99%
“…A phenomenon similar to that observed in the present study has been reported in heat-treated foods, where damaged cells are unable to repair and tend to die in unfavorable environments (Lestiner, 1996). In addition, an extension of the lag time in the growth of the surviving cells in foods with radiation-related injuries were reported (Grant & Patterson, 1992;Jo et al, 2005aJo et al, , 2005b. After inoculation before freezing, the population of S. typhimurium was about 10 7 CFU/g ( Table 6).…”
Section: Inoculation Testmentioning
confidence: 93%